Viewpoint: Toward the Genetic Architecture of Disease Severity in Inflammatory Bowel Diseases. Issue 7 (17th May 2018) - Liefferinckx, Claire; Franchimont, Denis
Abstract: Inflammatory bowel disease (IBD) is characterized by uneven disease courses with various clinical outcomes. A few prognostic markers of disease severity may help stratify patients and identify those who will benefit the most from early aggressive treatment. The concept of disease severity remains too broad and vague, mainly because the definition must embrace several disease mechanisms, mainly inflammation and fibrosis, with various rates of disease progression. The magnitude of inflammation is an obvious key driver of disease severity in IBD that ultimately influence disease behavior. Advances in the genetics underlying disease severity are currently emerging, but attempts to overlap the genetics of disease susceptibility and severity have until now been unsatisfactory, suggesting that the genetic architecture of disease severity may be distinct from the genetics of disease susceptibility. In this review, we report on the current knowledge on disease severity and on the main research venues to decipher the genetic architecture of disease severity.